1992
DOI: 10.1007/bf01204107
|View full text |Cite
|
Sign up to set email alerts
|

Relation between antisperm antibodies and the rate of fertilization of human oocytes in vitro

Abstract: To clarify further the role of antisperm antibodies in in vitro fertilization, the occurrence of antisperm antibodies on ejaculated sperm and in sera was determined by the immunobead binding assay in 67 couples after an unsuccessful in vitro fertilization cycle. Antisperm antibodies in maternal sera were associated with a failure of oocyte fertilization (P less than 0.02) or with fertilization of only 9-19% of the oocytes (P less than 0.01) in vitro. Antisperm antibodies were detected in sera from 13 of 24 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 13 publications
0
10
0
2
Order By: Relevance
“…This binding may interfere with the fertilization process in vivo and in vitro. In fact, Witkin et al [42] reported on the examination by the IBT of 67 couples after an unsuccessfid IVF cycle that sperm-bound antibodies were detected in 35.7% (5/14) of men with poor fertilization rate (9-19%) and in none (0/19) of the patients with greater than 40% fertilization rate 0) < .02). Recently, Ford et al [43] demonstrated a significantly lower fertilization rate (up to cleaving, 38%, 209/544) of mature oocytes in cases of positive IBT in the seminal plasma than that (68%, 380/555; p < .001) of the control group.…”
Section: Malementioning
confidence: 99%
“…This binding may interfere with the fertilization process in vivo and in vitro. In fact, Witkin et al [42] reported on the examination by the IBT of 67 couples after an unsuccessfid IVF cycle that sperm-bound antibodies were detected in 35.7% (5/14) of men with poor fertilization rate (9-19%) and in none (0/19) of the patients with greater than 40% fertilization rate 0) < .02). Recently, Ford et al [43] demonstrated a significantly lower fertilization rate (up to cleaving, 38%, 209/544) of mature oocytes in cases of positive IBT in the seminal plasma than that (68%, 380/555; p < .001) of the control group.…”
Section: Malementioning
confidence: 99%
“…The effects of ASA on sperm functions are very heterogeneous, as they may impair different steps of the fertilization process. ASA are described to reduce cervical mucus penetration [1,2], reduce or increase capacitation and acrosome reaction [3,4], inhibit the binding of the zona pellucida [5,6] and oolema binding, and affect the sperm-egg fusion [7,8] and the embryonic development, implantation and miscarriages [9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…La corr6-lation n6gative avec le taux de grossesses en FIV est fonction du pourcentage et de la localisation des anticorps li6s aux gametes (> 90%), et de leur type [1,16,67,110,111]. Cette alt6ration intervient ~ plusieurs niveaux du processus de f6condation : 9 perturbation de la r6action acrosomique par rupture pr6-matur6e de l'acrososme et/ou par blocage de la capacitation [6,35,41,110] ; 9 diminution de l'attachement h, et de la p6n6tration dans la zone pellucide entrainant une diminution du pourcentage de f6condation [1,41,65,99,107]. Une 6tude r6cente suggbre que ce n'est pas l'attachement ?~ la zone pellucide qui serait modifi6 mais plut6t l'induction de la r6action acrosomique par celle-ci [35] ; 9 la fusion avec l'ovocyte serait emp~ch6e par des anticorps dirig6s contre les antig~nes de la membrane interne de l'acrosome [65].…”
Section: Effets Sur Les Interactions Ovocyte-spermatozo'idesunclassified